Reversing direct factor Xa or thrombin inhibitors: Factor V addition to prothrombin complex concentrate is beneficial in vitro. Issue 3 (25th April 2022) - Brinkman, Herm Jan M.; Swieringa, Frauke; Zuurveld, Marleen; Veninga, Alicia; Brouns, Sanne L. N.; Heemskerk, Johan W. M.; Meijers, Joost C. M.
Abstract: Background: Prothrombin complex concentrate (PCC) is a human plasma‐derived mixture of partially purified vitamin K‐dependent coagulation factors (VKCF). Current therapeutic indication is treatment and perioperative prophylaxis of bleeding in acquired VKCF deficiency. Off‐label uses include treatment of direct factor Xa‐ or thrombin inhibitor‐associated bleeds, treatment of trauma‐induced coagulopathy, and hemorrhagic complications in patients with liver disease. Objective: Considering PCC as a general prohemostatic drug, we argued that its clinical efficacy can benefit from supplementation with coagulation factors that are absent in the current PCC formulation. In this study, we focused on factor V. Methods: We mimicked a coagulopathy in vitro by spiking whole blood or derived plasma with the direct oral anticoagulants (DOAC) rivaroxaban or dabigatran. We studied DOAC reversal by PCC and factor V concentrate (FVC) using a thrombin generation assay, thromboelastography, fibrin generation clot lysis test, and microfluidic thrombus formation under flow. Results: In DOAC‐treated plasma, PCC increased the amount of thrombin generated. The addition of FVC alone or in combination with PCC caused a partial correction of the thrombin generation lag time and clotting time. In DOAC‐treated whole blood, the combination of PCC and FVC synergistically improved clotting time under static conditions, whereas complete correction of fibrin formation was observed under flow. Clot strength and clot resistance toward tissue plasminogen activator‐induced lysis were both increased with PCC and further enhanced by additional FVC. Conclusion: Our in vitro study demonstrates a beneficial effect of the combined use of PCC and FVC in DOAC reversal.